2015
DOI: 10.1111/febs.13576
|View full text |Cite
|
Sign up to set email alerts
|

Soluble TL1A is sufficient for activation of death receptor 3

Abstract: Death receptor 3 (DR3) is a typical member of the tumor necrosis factor receptor family, and was initially identified as a T-cell co-stimulatory molecule. However, further studies revealed a more complex and partly dichotomous role for DR3 and its ligand TL1A under (patho)physiological conditions. TL1A and DR3 are not only a driving force in the development of autoimmune and inflammatory diseases, but also play an important role in counteracting these processes through an increase in the number of regulatory T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…In line with this, subsequent studies demonstrated that cIAP depletion using small molecules mimicking the function of the second mitochondria‐derived activator of caspases (SMAC) disrupted complex I formation and NFκB signaling . Our lab extended these findings and showed that in the absence of cIAPs DR3 stimulation allowed full‐blown apoptosis induction in the leukemia cell lines TF‐1 and Ku812F . Notably, DR3 expression has also been reported in B cells isolated from patients with chronic lymphocytic leukemia .…”
Section: Molecular Mechanisms Of Dr3 Signalingsupporting
confidence: 70%
“…In line with this, subsequent studies demonstrated that cIAP depletion using small molecules mimicking the function of the second mitochondria‐derived activator of caspases (SMAC) disrupted complex I formation and NFκB signaling . Our lab extended these findings and showed that in the absence of cIAPs DR3 stimulation allowed full‐blown apoptosis induction in the leukemia cell lines TF‐1 and Ku812F . Notably, DR3 expression has also been reported in B cells isolated from patients with chronic lymphocytic leukemia .…”
Section: Molecular Mechanisms Of Dr3 Signalingsupporting
confidence: 70%
“…Fc-FLAG-scTRAIL was generated by in-frame insertion of FLAG-scTRAIL [47] into a pCR3 variant encoding the IgG1 Fc domain and a linker (kind gift from P. Schneider, Department of Biochemistry, University of Lausanne). Recombinant Fc-FLAG-TRAIL was produced in HEK293 cells as previously described for TL1A [48]. …”
Section: Methodsmentioning
confidence: 99%
“…As TNFSF15 and IL24 are secreted factors implicated in apoptotic pathways [33, 34], which were upregulated in the paclitaxel-residual cells (Figure 4B, 4J; Figure 5C, 5D), they might sensitize paclitaxel-residual cells to BV6 via an autocrine loop, and thus, could also sensitize naïve or PTX R cells to this inhibitor. To explore this possibility, we incubated naïve and PTX R MDA-MB-231 and SUM159T cells with supernatants of their paclitaxel-residual counterparts and examined their response to BV6.…”
Section: Resultsmentioning
confidence: 99%